2002
DOI: 10.1105/tpc.010339
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of a Fluorescent Marker in Plant Cells Is Sensitive to Brefeldin A and Wortmannin

Abstract: We assessed FM1-43 [ N -(3-triethylammoniumpropyl)-4-(4-[dibutylamino]styryl)pyridinium dibromide] as a fluorescent endocytosis marker in intact, walled plant cells. At 4 ؇ C, FM1-43 stained the plasma membrane, and after 30 to 120 min of incubation at 26 ؇ C, FM1-43 labeled cytoplasmic vesicles and then the vacuole. Fluorimetric quantitation demonstrated dye uptake temperature sensitivity ( ‫ف‬ 65% reduction at 16 ؇ C, Ͼ 90% at 4 ؇ C). FM1-43 uptake in suspension cells was stimulated more than twofold by bref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
184
4
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(203 citation statements)
references
References 76 publications
13
184
4
2
Order By: Relevance
“…In addition, GFP-Flot1 was also found to colocalize partially with FM4-64. Given that this FM4-64 dye is internalized, via endocytosis from the plasma membrane, and is considered to be a bona fide marker for the endocytic pathway in plant cells (Emans et al, 2002;Chintagari et al, 2006), our findings offer strong support for the hypothesis that Flot1 participates in an endocytic pathway.…”
Section: Flot1 Participates In Non-clathrin-mediated Endocytosissupporting
confidence: 69%
“…In addition, GFP-Flot1 was also found to colocalize partially with FM4-64. Given that this FM4-64 dye is internalized, via endocytosis from the plasma membrane, and is considered to be a bona fide marker for the endocytic pathway in plant cells (Emans et al, 2002;Chintagari et al, 2006), our findings offer strong support for the hypothesis that Flot1 participates in an endocytic pathway.…”
Section: Flot1 Participates In Non-clathrin-mediated Endocytosissupporting
confidence: 69%
“…To test this hypothesis, we loaded Arabidopsis root hairs with 2 M of the amphiphilic styryl dye FM4-64, which is internalized by endocytosis (Fischer-Parton et al, 2000). (A similar amphiphilic styryl dye, FM 1-43, was discussed by Emans et al [2002].) The loading of root hairs with this dye, pretreated and grown in 0.5 M CD, was not inhibited as expected.…”
Section: Resultsmentioning
confidence: 99%
“…FM4-64, a fluorescent styryl dye that is internalized via endocytosis from the PM to the lytic vacuole, serves as a marker for the endocytic pathway in plant cells (Emans et al, 2002;Tse et al, 2004;Lo and Jiang, 2006). We previously demonstrated that FM4-64 colocalizes with the PVC marker YFP-BP-80 but not the Golgi marker GONST1-YFP in transgenic BY-2 cells (Tse et al, 2004), indicating that the secretory and endocytic pathways merge in PVCs.…”
Section: Yfp-scamp1-labeled Organelles Are Early Endosomesmentioning
confidence: 99%
“…In addition, the fluorescent dyes FM4-64 and FM1-43 have been successfully used to study the endocytic pathway in plant cells. After their insertion in the PM, these styryl dyes pass through endosomal compartments on their way to the tonoplast (Vida andEmr, 1995, Kim et al, 2001;Ueda et al, 2001;Emans et al, 2002;Tse et al, 2004;Dettmer et al, 2006). Therefore, colocalization of proteins with internalized FM4-64 may be used to judge whether a particular compartment labeled by a specific protein is a putative endosomal compartment in plant cells.…”
Section: Introductionmentioning
confidence: 99%